Ambiente de aprendizaje y el nivel académico de los estudiantes en la Escuela de Educación Básica “Carlos Darwin”, de la Parroquia Pimocha, cantón Babahoyo, Provincia de Los Ríos - Quila Borja, Isabel del Rocio (2019)
The learning environments are of great importance for the improvement of the academic performance of the students of the basic education school “Carlos Darwin”, of the Pimocha parish, Babahoyo canton, province of Los Ríos. In this research it was observed that there are different types of learning environments, however, not all of them are practiced correctly, which is why there is a concern of the low performance of students so that teachers should be trained in a way constant so that students achieve the desired academic achievement in a positive way in academic performance. With the constant training and with the help of the parents, the learning environments will increase in a positive way. The beneficiaries will be the students and teachers of the School of Basic Education "Carlos Darwin", in addition the institution will have a reference to potentiate the environments of learning leading to a significant improvement in the quality of education of the institution. The learning environment is an area in which the student is developing and needs space in which he must perform different activities to exercise or move that conform to the dimensions and rules of the operation of each of the sites. Surveys were also carried out on teachers and parents to see how much knowledge they have about learning environments for students' academic development and performance, where it was concluded that many teachers and parents do not have the knowledge Necessary about learning environments, however, they try to make students improve their academic performance with different study techniques and strategies, even though in the basic education school "Carlos Darwin", this situation is sought to improve because the lack of knowledge about learning environments because it not only lowers the student's academic performance but also that of the same institution